Pengabdian Kepada Masyarakat RT 03 RW 05 di Desa Pandak Sidoharjo Kabupaten Sragen - Ameliana Friskia Rahmadini; Isri Nasifah; Monalisa; Roja’ah (Universitas Ngudi Waluyo, 2022)
Family study practice (PPK) is one of the student activities that must be carried out where it is a real form of work in providing Community Midwifery Care Services, where community midwifery is one of the courses in the Community Midwifery Profession curriculum with the aim of implementing comprehensive Midwifery practice by paying attention to culture. society in a community setting with a midwifery management approach and based on the concept of professional skills and attitudes. After following the Family Study Practice (PPK) students are expected to be able to identify, plan, prioritize, implement, and evaluate the management of community midwifery services with community movement and empowerment techniques and educational approaches to individuals, families, special groups or in certain communities in achieving the SDGs. In the implementation of this community midwifery practice, the assessment was carried out by means of direct interviews, immediate implementation and secondary data collection. After carrying out health education and practicing activities, the knowledge of the residents, both prospective brides, pregnant women, toddlers and postpartum mothers, there were some who lacked knowledge, and after carrying out health education about each of the materials provided, such as counseling on reproductive health of prospective brides, counseling on balanced nutrition and presentations for toddlers, oxytocin massage, yoga for pregnant women, giving oxytocin massage to postpartum mothers. Furthermore, the post test was carried out to experience an increase after the post test was carried out. The conclusion of the implementation activities carried out in the village of Pandak Sidoharjo Sragen found several problems that occurred, namely the taboo on knowledge of the bride and groom, balanced nutrition and serving for toddlers, lack of pregnant women for maternity care so that pregnant women were given yoga, and live demonstration of oxytocin massage for postpartum mothers. Abstrak Praktik pengkajian Keluarga (PPK) merupakan salah satu kegiatan mahasiswa yang harus dilaksanakan dimana suatu bentuk kerja nyata dalam memberikan Pelayanan Asuhan Kebidanan Komunitas, dimana kebidanan komunitas ini merupakan salah satu mata kuliah dalam kurikulum Profesi Kebidanan Komunitas dengan tujuan melaksanankan praktik Kebidanan secara komperehensif dengan memperhatikan budaya masyarakat dalam tatanan di Komunitas dengan pendekatan manajement kebidanan dan didasari oleh konsep keterampilan dan sikap Profesional.Setelah mengikuti Praktik pengkajan Keluarga (PPK) diharapkan mahasiswa mampu mengidentifikasi, merencanakan, memprioritaskan, mengimplementasikan, dan mengevaluasi manajement pelayanan kebidanan komunitas dengan teknik pergerakan dan pemberdayaan masyarakat serta pendekatan edukasi pada individu, keluarga, kelompok khusus ataupun pada komunitas tertentu dalam mencapai SDG’s. Dalam pelaksanaan praktik kebidanan komunitas ini pengkajian dilakukan dengan cara wawancara langsung, Pelaksanaan secara langsung dan pengambilan data sekunder. Setelah dilakukan pendidikan kesehatan dan adanya praktik kegiatan, pengetahuan warga baik calon pengantin, ibu hamil, balita dna ibu nifas, ada beberapa yang berpengetahuan kurang, dan setelah dialkukan pendidikan kesehatan tentang masing-masing materi yang diberikan seperti penyuluhan kespro calon pengantin, penyuluhan gizi seimbang dan penyajian untuk balita, pijat oksitosin, yoga ibu hamil, diberikan pijat oksitosin kepada ibu nifas. Selanjutnya dilakukan post test mengalami pengingkatan setelah dilakukan post test. Kesimpulan dari kegiatan pelaksanaan yang dilakukan di desa pandak sidoharjo sragen ditemukan beberapa masalah yang terjadi yaitu tabunya pengetahuan calon pengantin, gizi seimbang dan penyajian untuk balita, kurangnya ibu hamil untuk oleharga sehingga diberikan yoga ibu hamil, dan peragaan secara langsung pijat oksitosin pada ibu nifas.